GPCR Heterodimerization in the Reproductive System: Functional Regulation and Implication for Biodiversity - Satake, Honoo; Matsubara, Shin; Aoyama, Masato; Kawada, Tsuyoshi; Sakai, Tsubasa (Frontiers in Endocrinology, 2013)
A G protein-coupled receptor (GPCR) functions not only as a monomer or homodimer but also as a heterodimer with another GPCR. GPCR heterodimerization results in the modulation of the molecular functions of the GPCR protomer, including ligand binding affinity, signal transduction, and internalization. There has been a growing body of reports on heterodimerization of multiple GPCRs expressed in the reproductive system and the resultant functional modulation, suggesting that GPCR heterodimerization is closely associated with reproduction including the secretion of hormones and the growth and maturation of follicles and oocytes. Moreover, studies on heterodimerization among paralogs of gonadotropin-releasing hormone (GnRH) receptors of a protochodate, Ciona intestinalis, verified the species-specific regulation of the functions of GPCRs via multiple GnRH receptor pairs. These findings indicate that GPCR heterodimerization is also involved in creating biodiversity. In this review, we provide basic and current knowledge regarding GPCR heterodimers and their functional modulation, and explore the biological significance of GPCR heterodimerization.